"I'm Not Gonna Be Like 'That Guy'": Examining Antidrug Shock Advertising through the Eyes of "That Guy". Issue 2 (1st February 2017) - Ferestad, Jaysen; Thompson, Melissa
ABSTRACT: Shock advertising antidrug campaigns pose significant implications for methamphetamine (meth) addicts. In recent years, the Montana Meth Project public service campaign has broadcast a series of advertisements containing shocking and disturbing images of meth addicts in an attempt to prevent meth use. Although intended to warn teens about the dangers of meth, the shock-based advertising reaches another population: meth addicts, unintentionally exposing them to a labeling process. This study examines the effects of Montana's advertisements on the worldview of 20 recovering meth addicts using interviews. Results highlight the unintended consequences of shock advertising on those attempting to reintegrate into the non-using community, suggesting that the campaign negatively impacts addicts' worldviews and creates stereotypes, stigma, and differential treatment of meth users. Ultimately, this antidrug scare campaign appears to be a barrier to reintegration for meth addicts.